Evaluasi Kualitas Thrombocyte Concentrate (TC) Berdasarkan Kadar pH, Level Kekeruhan, dan Swirling Selama Masa Penyimpanan 5 Hari - Aulia Rahman; Wiwit Sepvianti; Arif Tirtana; Gravinda Widyaswara; Kumara Rahmawati Zain (Jurnal Kesehatan Rajawali, 2023)
Thrombocyte concentrate transfusion was one of the important medical treatments in increasing the number of thrombocytes in patients with medical indications of thrombocytopenia. The monitoring of blood product quality from upstream to downstream must be considered in order to obtain a good quality thrombocyte concentrate. Thrombocyte concentrate was prone to change during storage due to significant changes between in vitro and in vivo conditions. The changes in thrombocyte concentrate quality that commonly occur during storage were the decreased platelet levels, increased of acidity (pH) and turbidity, and loss of thrombocyte swirling in the plasma. Therefore, it was necessary to conduct research to determine the quality of thrombocyte concentrates during the 5-day shelf life to find out whether at the end of the shelf life, these blood products were still suitable for transfusion to the patients. Several tools used in this study were Hematology Analyzer, blood scales, and pH meter. The results of successive studies showed that the thrombocyte concentrate product did not meet the basic quality standards because the number of thrombocytes per unit was below the standard that was set by Regulation of the Ministry of Health of the Republic of Indonesia Number 91 Years 2015.